Anatomic Factors Associated With the Development of an Anterior Cruciate Ligament Rerupture in Men: A Case-Control Study. Issue 12 (October 2022) - Misir, Abdulhamit; Uzun, Erdal; Sayer, Gokhan; Guney, Betul; Guney, Ahmet
Background: Although several factors are associated with anterior cruciate ligament (ACL) rerupture, the effect of anatomic factors associated with ACL rupture on ACL rerupture development has not been evaluated. Purpose: To determine individual anatomic parameters independently associated with ACL rerupture and the diagnostic values of these parameters. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 91 male patients with ACL rerupture and 182 age-, sex-, body mass index–, and side dominance–matched patients without rerupture who underwent ACL reconstruction with a 5-year follow-up were included. In all, 35 parameters that were previously defined as risk factors for primary ACL rupture were compared between the 2 groups. Uni- and multivariate logistic regression models were created to evaluate independently associated factors. Receiver operating characteristic curve analysis was performed for independently associated parameters to predict sensitivity, specificity, and cutoff values. Results: The mean ± standard deviation age of patients at the time of index surgery was 26.5 ± 6.7 years. Notch shape index ( P = .014), tibial proximal anteroposterior (AP) distance (TPAPD) ( P < .001), lateral femoral condylar AP distance (LCAPD)/TPAPD ratio ( P < .001), medial meniscal cartilage bone height ( P < .001), and lateral meniscal bone angle ( P = .004) were found to be significantly different between the 2 groups. Only the LCAPD/TPAPD ratio (odds ratio, 2.713; 95% CI, 1.998-5.480; P < .001) was found to be independently associated with ACL rerupture development. The LCAPD/TPAPD ratio revealed 78.9% sensitivity and 75.5% specificity (area under the curve, 0.815; 95% CI, 0.760-0.870) for values above 1.52. Conclusion: The LCAPD/TPAPD ratio can be used to distinguish patients who are at risk of developing ACL rerupture from patients who are not. In the clinical practice, findings of this study may help to develop surgical and nonsurgical preventive strategies in ACL rerupture development.